Perancangan Buku Foto “Serangga Di Sekitar Kita” - I Made Surya Dharma Yasa; Gunawan Susilo; Ahmad Zakiy Ramadhan (LPPM STIKI Malang, 2021)
This research aims to design a photo book as an introduction to insects around us for children aged 6-12 years. The problem in this design is that there are still many children who do not know about harmful and harmless insects. As an effort to overcome this problem is to make a photo book design. This design aims as an introduction to insects around us. This design uses the method of Platter Design Thinking (2012) as a design reference consisting of (a) empathize, (b) define, (c) ideate, (d) prototype, and (e) test. The final result of this design is a photo book containing introductions such as habitat, food, dangerous and harmless.